2018
DOI: 10.1186/s12885-018-4292-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of angiotensin-converting enzyme inhibitors and angiotensin II receptor blockers in chemoprevention of hepatocellular carcinoma: a nationwide high-risk cohort study

Abstract: BackgroundResearch has revealed that angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin II receptor blockers (ARBs) may prevent cancers such as hepatocellular carcinoma (HCC). The comparative chemopreventive effects of ACEIs and ARBs in high-risk populations with hepatitis B virus (HBV) or hepatitis C virus (HCV) infection have yet to be investigated.MethodsFrom 2005 to 2014, high-risk HBV and HCV cohorts of hypertensive patients without HCC history were recruited from three linked national datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 50 publications
0
27
3
Order By: Relevance
“…It is interesting, however, to note that the HCC risk among participants receiving anti-hypertensive agents was 1.94fold higher than that among those not receiving such agents (95% CI = 1.45-2.6, p < 0.001; Table 2). Although our present findings cannot explain this conflict, Ho et al [24] found that the use of angiotensin-converting enzyme inhibitors and angiotensin II receptor blockers was associated with higher HCC occurrence in patient subgroups consisting of patients with no cirrhosis, no DM, and no hyperlipidemia. This issue requires further study in the future.…”
Section: Discussioncontrasting
confidence: 82%
“…It is interesting, however, to note that the HCC risk among participants receiving anti-hypertensive agents was 1.94fold higher than that among those not receiving such agents (95% CI = 1.45-2.6, p < 0.001; Table 2). Although our present findings cannot explain this conflict, Ho et al [24] found that the use of angiotensin-converting enzyme inhibitors and angiotensin II receptor blockers was associated with higher HCC occurrence in patient subgroups consisting of patients with no cirrhosis, no DM, and no hyperlipidemia. This issue requires further study in the future.…”
Section: Discussioncontrasting
confidence: 82%
“…It is interesting, however, to note that the HCC risk among participants receiving anti-hypertensive agents was 1.94-fold higher than that among those not receiving such agents (95% CI = 1.45-2.6, p < 0.001; Table 2). Although our present findings cannot explain this conflict, Ho et al [24] found that the use of angiotensin-converting enzyme inhibitors and angiotensin II receptor blockers was associated with higher HCC occurrence in patient subgroups consisting of patients with no cirrhosis, no DM, and no hyperlipidemia. This issue requires further study in the future.…”
Section: Discussioncontrasting
confidence: 82%
“…Six more recent retrospective observational studies evaluated the effect of ACE-Is or ARBs on overall survival (OS) and/or time to recurrence in patients who underwent different HCC treatments (Table 1). Ho et al[16] evaluated the effect of ACE-I or ARB exposure within the first six months after initiating antiviral agents in a high-risk HBV and HCV large cohorts of patients and did not find any protective effect of these drugs on HCC development adjusted for potential confounders. Surprisingly, in HCV patients without cirrhosis, diabetes, and hyperlipidemia, they found an increased HCC risk associated with ACE-I or ARB use in (HR = 4.53, 95%CI: 1.46-14.1).…”
Section: Resultsmentioning
confidence: 99%
“…The more recent human studies are all observational retrospective cohort or case-control studies[7,16-21]. All these studies evaluated the effect of ACEIs and/or ARBs on overall survival.…”
Section: Discussionmentioning
confidence: 99%